Analisis Penerapan Sistem Pemerintahan Berbasis Elektronik (SPBE) dalam Meningkatkan Efisiensi Pelayanan Publik di Indonesia - Niken Febiana Putri Pakaya; Princenoel Wanei; Herni Herawati Elisabeth Abraham; Yaulie Deo Y. Rindengan; Ade Yusupa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The digital transformation of government through the implementation of the Electronic-Based Government System (SPBE) is a strategic effort to establish effective, efficient, transparent, and accountable governance. This study aims to analyze the implementation level of SPBE in Indonesia and its contribution to improving public service efficiency. The main issues identified include technological adoption gaps among institutions, limited digital infrastructure, low system interoperability, and uneven digital human resource capacity. This research employs a descriptive analytical approach by reviewing relevant regulations such as Presidential Regulation No. 95 of 2018 on SPBE and national SPBE index data in 2024, which recorded a score of 3.12 categorized as “Good.” Furthermore, the UN E-Government Survey 2024 placed Indonesia at 64th among 193 countries, indicating significant progress in digital government transformation. The analysis results show that SPBE implementation positively influences public service efficiency, particularly in speeding up service delivery, reducing operational costs, and enhancing transparency. However, successful implementation depends on policy synergy, infrastructure readiness, and the improvement of digital competency among civil servants. Therefore, integration strategies and cross-agency capacity building are essential to accelerate Indonesia’s digital government transformation.